Media Sosial dan Tantangan di Era Digital : Penelitian - Karmila Azzahra; Astri Triyanti; Yulia Desi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Social media has become a vital component of modern life in the digital era, influencing various sectors such as communication, education, economy, and politics. Platforms like Facebook, Instagram, Twitter, and TikTok enable rapid information exchange and real-time interaction across regions. Despite its many advantages, social media also presents significant challenges, including the spread of misinformation, violations of personal data privacy, digital addiction, cyberbullying, and the growing polarization of public opinion. Additionally, platform algorithms often reinforce narrow perspectives and create closed information spaces (filter bubbles), which can hinder critical thinking. Therefore, enhancing digital literacy and implementing appropriate regulations are essential to minimizing negative impacts and promoting responsible social media use. This study aims to evaluate the role of social media and the challenges it poses, while offering solutions to foster a healthier and more accountable digital ecosystem.